STRENGTHENING CHARACTER EDUCATION BASED ON LOCAL WISDOM IN ELEMENTARY SCHOOLS THROUGH PARTICIPATION IN THE SOWAN NGALAS TRADITION - Isa Bowo Yunianto; Sriyanto (SOSIOEDUKASI, 2026)
Strengthening character education in elementary schools is crucial, but it still requires a contextual approach based on local wisdom to make character values ​​more meaningful for students. This study aims to analyze the strengthening of local wisdom-based character education in elementary schools through participation in the Sowan Ngalas Tradition. The study used a qualitative ethnographic approach with students and teachers at SDN 1 Pesangkalan as subjects, as well as community leaders. Data were collected through participant observation, in-depth interviews, and documentation. Data were analyzed thematically through data reduction, data presentation, and conclusion drawing. Data were validated through triangulation of sources and techniques. The results of the study indicate that the Sowan Ngalas tradition plays an important role in strengthening local wisdom-based character education in elementary schools. Through a participatory approach, students gain authentic experiences that enrich their understanding of character values ​​in a more meaningful way. Religious, nationalist, mutual cooperation, integrity, and independent characters can be internalized through a series of concrete cultural practices. Religious values ​​grow through communal prayer and the procession of washing heirlooms; nationalism develops through the procession of heirlooms and the narrative of village history; mutual cooperation is built through collective work in the mountain procession; integrity is strengthened through reflection on moral values ​​in the shadow puppet performance; and independence is formed through responsibility for maintaining cleanliness and caring for the environment after the activity. These findings confirm that direct experiences based on local culture provide meaningful, reflective, and contextual character learning for students' lives. Collaboration between schools, community leaders, and local communities is key to maintaining the sustainability of regional traditions while instilling character values ​​from an early age.